52. MULTIPLE DISPLACEMENT AMPLIFICATION CAN INCREASE THE DIAGNOSTIC EFFICIENCY IN PGT-M FOR THALASSEMIA. (August 2019) - Shen, X.; Fu, Y.; Chen, D.; Xu, Y.; Ding, C.; Zhong, Y.; Xu, Y.; Zhou, C.
Abstract : Introduction: Preimplantation genetic testing for monogenic diseases (PGT-M) has been widely conducted to prevent the birth of children genetically affected with thalassemia, especially in southeast China. However, due to the insufficient DNA template available from an embryo-level biopsy, its detection efficiency is still far from satisfactory. A suitable whole genome amplification (WGA) method is crucial to the success of PGT-M. This study aims to evaluate whether using multiple displacement amplification (MDA) as the first step can increase the diagnostic efficiency of PGT-M for thalassemia disorders. Material & methods: This is a retrospective cohort study. All included patients underwent PGT-M cycles (n=939) for β-thalassemia-SEA or β- thalassemia in our center from January 2014 to February 2018. We divided the patients into two groups based on two different detection methods. For the polymerase chain reaction (PCR) group (n=428), after cell lysis we directly conducted fluorescent gap PCR for β-thalassemia-SEA diagnosis or multiplex nested PCR+ reverse dot blot (RDB) analysis for β- thalassemia diagnosis. For the MDA group (n=511), the whole genomes of single cells were directly amplified using MDA before fluorescent gap PCR or singleplex PCR+RDB procedures. Results: A total of 7756 embryos were tested. The overall diagnostic efficiency of the MDA group was significantly higher than that of the PCR group (96.70% vs 86.60%, P <0.001). The percentage of embryos available for transfer was significantly higher in the MDA group than in the PCR group (72.64% vs 62.84%, P <0.001). Furthermore, the carrier embryo rate of the MDA group was significantly higher than that of the PCR group (47.81% vs 32.67%, P <0.001). Conclusions: This study indicates that MDA, as the universal first step in PGT-M for β-thalassemia and β-thalassemia, can increase 10.10% diagnostic efficiency, thus may provide a better choice for the clinical PGT-M practice.